NEW CUCUMBER VARIETIES OF VNIISSOK SELECTION - I. B. Korottseva (Овощи России, 2012)
Cucumber is the one of the leading vegetable crops grown in the open and protected ground of the Russian Federation. However, in recent years the production area of this crop decreased because of a number of reasons, one of which is the loss of cucumber crops from diseases. The most economical and environmentally safe method of cucumber protection from diseases is the development and utilization of resistant varieties. By selection on artificial and natural infective zones in VNIISSOK a new variety of cucumber Vodopad and parthenocarpic hybrid F1 Krasotka have been developed.